Graphene based composite membranes for environmental toxicology remediation, critical approach towards environmental management. (November 2022) - Lopez-Fernandez, Miriam; Tariq, Sadaf; Naseem, Khalida; Ahmad, Awais; Khan, Safia; Younas, Umer; Javed, Muhammad Sufyan; Fan, Wong Siew; Luque, Rafael; Ali, Shafaqat
Abstract: Graphene-based composite membranes, as laminated, stacked, and assembled architectures of graphene, have surpassed other conventional membranes with their advanced and preeminent structural specialization and potential use in a wide range of sustainable and environmental applications. The characteristic membrane features such as distinct laminar morphology, tailored physicochemical properties, as well as extraordinary molecular properties have fascinated scientists. Due to remarkable mechanical properties, these membranes can be easily fabricated. Recent progress has been achieved by graphene and its derivatives-based membranes to purify water and gases for environmental remediation. This review explained the latest and groundbreaking advances in chemical design, fabrication, and application of graphene-based membranes. Special attention is paid to the recent developments on graphene-based composites into membranes with various forms: free-standing, layered, and graphene-based nanocomposite membranes. Furthermore, a unique approach on environmental management with as-fabricated membranes is provided by discussing the effect of physicochemical properties. Consequently, their full-scale use for environmental management, water purification, gas purification, and biological treatments will pave the way for their promising features and realize their future prospects. Graphical abstract: Image 1 Highlights: Design, fabrication, and application of graphene-based membranes. Critical approach on environmental management with graphene-fabricated membranes. Graphene-based nanocomposites with high specific surface area, cost-effectiveness, remarkable porosity. Graphene base Membrane, A promising Material for wastewater treatment.